Translating Monastic Lessons to Teaching Undergraduate Biology - Pierce, B. Daniel (Frontiers in Communication, 2021)
My participation in the Emory Tibet Science Initiative (ETSI) has afforded me considerable means to enrich my teaching at the undergraduate level. Here, I discuss how I translated lessons learned from working with Tibetan Monks to teaching in a primarily undergraduate institution, including: 1) introducing each course with a challenge to the assumptions made as “Western scientists” 2) using the unique monastic pedagogy of debate to facilitate classroom scholarship, and 3) embracing compassion as a central tenet to engage and empower student learning, which has become the cornerstone of my teaching philosophy. In addition, I brought undergraduates with me to participate , in ETSI and the experience had a profound effect on their educational and career paths. These experiences with the Tibetan monks transformed my teaching and continue to inform how I approach undergraduate education.